Thirtythree : A New Horizon of Photography at Moholy-Nagy University of Art and Design Budapest. - Kopeczky, Róna; Bakk, Ágnes Karolina; Kudász, Gábor Arion; Máté, Gábor; Szalontai, Ábel (Berlin : Hatje Cantz Verlag GmbH, 2018)
Ács, Alíz Veronika ; Bánhegyesy, Antal ; Bartha, Máté ; Biró, Dávid ; Bognár, Benedek ; Drégely, Imre ; Ember, Sári ; Fabricius, Anna ; Fátyol, Viola ; Ficsór, Zsolt ; Vinkó, Andi Gáldi ; Gulyás, Miklós ; Herczeg, Eszter ; Hermann, Ildi ; Hodosy, Enikő ; Koleszár, Adél ; Kovács, Alida ; Kovács, Katalin ; Kozó, Attila ; Kudász, Gábor Arion ; Lábady, István ; Ladocsi, András ; Lakos, Máté ; Máté, Balázs ; Máté, Gábor ; Misetics, Mátyás ; Molnár, Ágnes Éva ; Molnár, Zoltán ; Móró, Máté ; Nyíri, Julianna ; Péter, Ildikó ; Piti, Marcell ; Puklus, Peter ; Rácmolnár, Milán ; Rédling, Hanna ; Sivák, Zsófi ; Szalay, Krisztina ; Szalontai, Ábel ; Szatmári, Gergely ; Szombat, Éva ; Timár, Sára Erzsébet ; Törcsi, András ; Tóth, Barnabás ; Zagyvai, Sári ; Zana, Krisztián ; Zellei, Boglárka Éva
Thirtythree, Robert Capa Contemporary Photography Center, Budapest, 8 October, 2018 - 9 December, 2018
boek